2010
DOI: 10.1111/j.1365-2702.2010.03295.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diabetes mellitus, hypertension and obesity, and health‐related quality of life in Gaziantep, a central south‐eastern city in Turkey

Abstract: Patients with hypertension, obesity and diabetes mellitus need professional support from nurse. Frequent health-related quality of life evaluation and support is required for chronic patients, especially for those who are older, have lower educational and income levels and those with more than one chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
(103 reference statements)
2
30
0
2
Order By: Relevance
“…Patients' quality of life should be assessed by the nurse on a regular basis, and their educational needs should then be determined on the basis of the information gained. 19 In this study, the disease burden was found to be higher for patients who had another chronic illness in addition to diabetes and assessed quality of life and compliance to treatment as "poor. "…”
Section: Burden Of Oads/insulinmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients' quality of life should be assessed by the nurse on a regular basis, and their educational needs should then be determined on the basis of the information gained. 19 In this study, the disease burden was found to be higher for patients who had another chronic illness in addition to diabetes and assessed quality of life and compliance to treatment as "poor. "…”
Section: Burden Of Oads/insulinmentioning
confidence: 96%
“…16 Presence of other diseases accompanying the diabetes makes disease management of diabetic patients difficult 17 and impairs their quality of life. 18,19 Therefore, individuals who have 1 or more chronic conditions need to be supported, accepted, and understood so that they can have a healthy lifestyle, solve their problems, and improve their health-related quality of life. The role of the nurse is important in providing care for patients and responding their individual needs.…”
Section: Burden Of Oads/insulinmentioning
confidence: 99%
“…Heretofore a limited number of studies have been conducted in the Middle East to document the HRQoL of patients with T2DM [10][11][12][13]. Therefore the aim of this study was to measure HRQoL in Iranian patients with T2DM and examine which patient's sociodemographic and diabetes-related clinical characteristics are associated with better quality of life based on a nationally distributed sample.…”
Section: Introductionmentioning
confidence: 99%
“…O que torna o tratamento muito difícil, pois a grande maioria da medicação vai afectar negativamente a QV, através dos efeitos adversos ou através da alteração do estilo de vida associado á terapêutica crónica. Segundo alguns autores (Ucan & Ovavolu, 2010) a QV pode ser afetada pelo estado de saúde, e indicadores socioeconómicos como a pobreza, a baixa escolaridade e o desemprego. Estes dados estão de acordo com o nosso estudo, onde uma qualidade de vida superior em todas as dimensões foi observada nos doentes hipertensos com um nível mais elevado de escolaridade e que estavam a trabalhar na altura do estudo.…”
Section: Conclusõesunclassified